Indonesia's Role in Addressing Marine Plastic Waste Pollution in Southeast Asia Under the 1982 UNCLOS Framework - Harahap, Rahayu Repindowaty; Putra, Akbar Kurnia; Ramlan, Ramlan; Farisi, Mochammad (Uti Possidetis: Journal of International Law, 2025)
Marine plastic waste has become a significant environmental issue in Southeast Asia, prompting regional efforts to address its transboundary impact. As a member of ASEAN, Indonesia plays a strategic role in implementing international maritime environmental law, particularly the United Nations Convention on the Law of the Sea (UNCLOS) 1982. Objectives: This study aims to examine how ASEAN implements UNCLOS 1982 in tackling marine plastic pollution and to analyze Indonesia’s role in addressing this issue at both regional and national levels. Methodology: The research adopts a normative legal method with a statute approach, focusing on the legal norms within UNCLOS 1982 that pertain to marine environmental protection. Relevant ASEAN declarations and Indonesian national regulations are analyzed to assess their alignment with UNCLOS provisions. Findings: The study finds that ASEAN's implementation of UNCLOS 1982 includes a series of initiatives such as the ASEAN Conference on Reducing Marine Debris (2017), the Bangkok Declaration on Combating Marine Debris in the ASEAN Region (2019), and the ASEAN Framework of Action on Marine Debris. These instruments collectively establish a foundation for regional cooperation. Indonesia has actively participated in these initiatives and has reinforced its commitment through national measures, notably Presidential Regulation No. 83 of 2018 concerning Marine Debris Management, which includes a National Action Plan and the establishment of a National Coordination Team. Novelty: This study contributes to the understanding of Indonesia’s dual role in marine environmental governance-both as a regional actor in ASEAN and as a sovereign state implementing international obligations through national policy.